Significant Reduction in HIV Virologic Failure During a 15-Year Period in a Setting With Free Healthcare Access. (23rd October 2014) - Delaugerre, Constance; Ghosn, Jade; Lacombe, Jean-Marc; Pialoux, Gilles; Cuzin, Lise; Launay, Odile; Menard, Amélie; de Truchis, Pierre; Costagliola, Dominique; Abgrall, S.; Barin, F.; Billaud, E.; et al.
Abstract : The proportion of human immunodeficiency virus (HIV)-infected patients experiencing virologic failure during routine care fell markedly from 61.5% in 1997 to only 9.7% in 2009–2011, reflecting significant improvements (new drugs and guidelines) in HIV management in France over the last 15 years. Abstract: Background. Calendar trends in virologic failure (VF) among human immunodeficiency virus (HIV)-infected patients can help to evaluate the performance of healthcare systems and the need for new antiretroviral therapy (ART). We examined the time trend in the rate of VF beyond 6 months of ART between 1997 and 2011 in France. Methods. We included patients from the French Hospital Database on HIV who received at least 6 months of ART. VF was defined as 2 consecutive plasma HIV-RNA values >500 copies/mL or as 1 value >500 copies/mL followed by a treatment switch. We adjusted for patients' characteristics by fitting a multivariable generalized estimating equation logistic regression model with an exchangeable covariance matrix. Results. A total of 81 738 patients were enrolled, and median follow-up was 112.4 months. Median CD4 count was 333 cells/µL, and 23% of patients had HIV infection classified as Centers for Disease Control and Prevention stage C. Overall, 29.3% of patients received single/dual-drug ART initially, and 45.4% of patients experienced at least 1 episode of VF during follow-up. The percentage of patients with VF fell from 61.5% in 1997–1998 to 9.7% in 2009–2011 ( P < .0001). Factors associated with the lower frequency of VF were recent calendar period, a higher contemporary CD4 cell count, and first-line regimens based on nonnucleoside reverse transcriptase inhibitors or integrase inhibitors. Conclusions. The proportion of HIV-infected patients experiencing VF during routine care fell markedly between 1997 and 2009–2011, to only 9.7%. This was attributed to the advent of fully active and better-tolerated antiretroviral drugs, and to national guidelines recommending rapid management of VF after mid-2000.